Neuropathic pain drives anxiety behavior in mice, results consistent with anxiety levels in diabetic neuropathy patients. (May 2018) - Sieberg, Christine B.; Taras, Caitlin; Gomaa, Aya; Nickerson, Chelsea; Wong, Cindy; Ward, Catherine; Baskozos, Georgios; Bennett, David L.H.; Ramirez, Juan D.; Themistocleous, Andreas C.; Rice, Andrew S.C.; Shillo, Pallai R.; et al.
Abstract: Background: Epidemiological studies in patients with neuropathic pain demonstrate a strong association with psychiatric conditions such as anxiety; however, the precipitating pathology between these symptoms remains unclear. To investigate this, we studied the effects of lifelong stress on levels of neuropathic pain–like behavior and conversely, the effects of chronic neuropathic injury on anxiety-like status in male and female mice. In addition, we assayed this link in painful and painless diabetic peripheral neuropathy patients. Methods: Male and female mice were subject to ongoing life-stress or control living conditions. Baseline sensitivity and anxiety tests were measured followed by spared nerve injury (SNI) to the sciatic nerve. Subsequent sensory testing occurred until 3 weeks after SNI followed by anxiety tests between 4 and 6 weeks after SNI. Results: Levels of tactile or cold allodynia did not differ between adult mice subject to lifelong chronic stress, relative to nonstressed controls, for at least 3 weeks after SNI. By contrast, longer-term neuropathic mice of both sexes displayed pronounced anxiety-like behavior, regardless of exposure to stress. If sex differences were present, females usually exhibited more pronounced anxiety-like behavior. These ongoing anxiety behaviors were corroborated with plasma corticosterone levels in distinct animal groups. In addition, data from patients with painful and nonpainful diabetic neuropathy showed a clear relationship between ongoing pain and anxiety, with females generally more affected than males. Discussion: Taken together, these data demonstrate a strong link between chronic neuropathic pain and chronic anxiety, with the driver of this comorbidity being neuropathic pain as opposed to on-going stress. Abstract : Supplemental Digital Content is Available in the Text.